Factors influencing the use of e-wallet as a payment method among Malaysian young adults - Karim, Md Wasiul; Haque, Ahasanul; Ulfy, Mohammad Arije; Hossain, Md Alamgir; Anis, Md Zohurul (Research Publishing Academy (RPA), 2020)
In recent years, there is a noticeable increase of cashless transactions due to the development of financial technology. As a result of being expansion of fintech products such as e-wallet, consumers are shifting from cash-based to cashless. Young adult consumers in 21st century are regarded as tech-savvy as they were born in the era of smartphone technology. This study aims to examine the influencing factors for Malaysian young adults to use e-wallet as a payment method by applying extended technology acceptance model (TAM). Total of 330 data were collected from the users of e-wallet in the area of Klang Valley of Malaysia and analyzed by deploying partial least squares structural equation modeling (PLS-SEM). By applying two-step approach for instance, measurement model for indicator loadings, convergent validity, reliability and structural model for path analysis the findings from this study reveal that perceived usefulness, perceived ease of use and privacy and security have positive and significant relationship with behavioral intention to use e-wallet. This study helps the service providers of the digital marketplace further to have better understanding of the usefulness of using e-wallet for transaction purposes.